Extended Totally Extra-Peritoneal Repair (Etep) Vs Conventional Laparoscopic Repair With Defect Closure (Ipom Plus) For Umbilical Hernias: A Single-Center Study - Kenawadekar, Rahul; Patil , Tanmay; Bhavani , Sadyojata; Gokak, Akshay; Kiran, Ravi; H, Nithin.; Siddharth, Shrey; Shikhar, Saubhagya (Journal of Neonatal Surgery, 2025)
Background: General surgery professionals carry out umbilical hernia repair as a frequently repeating surgical procedure. Medical professionals have widely accepted IPOM repair with defect closure (called IPOM plus) for conventional intraperitoneal onlay mesh procedures. Medical professionals currently focus on extended totally extra-peritoneal repair (eTEP) because this procedure shows promise in decreasing postoperative complications as well as pain levels and improving recovery periods. Methods: The study performed in a single tertiary care center utilized a prospective observational approach when examining IPOM plus techniques and eTEP procedures for treating umbilical hernias. The researchers distributed sixty qualified patients between two groups: Group A (IPOM plus) and Group B (eTEP). The study tracked postoperative outcomes which included pain (Visual Analog Scale) measurement together with operative duration and hospitalization length and hernial complications like seroma and wound infection and recurrence. The manuscript displays numerical data using numbers alongside percentages as descriptive statistics. All data analysis used t-test combined with Fisher’s Exact test with chi-square test according to the appropriate scenario and accepted a significance level below 0.05. Results: The cohort participants had an average age of 48.15 years, although they showed a minor male majority throughout the study sample. Patients who underwent IPOM plus experienced procedure duration that was considerably shorter than patients in the other group. Postoperative pain ratings showed better results among eTEP patients who demonstrated lower scores during the time period from day 1 until day 7 and months 1 and 3 (p < 0.05). The eTEP group spent fewer days at the hospital than patients undergoing eTEP (6.8 days) (5.8 days) (p < 0.05). The risk of seroma formation together with wound infections remained similar for both patient groups. Conclusion: The eTEP hernia repair method outperforms IPOM plus surgery because it leads to shorter operative durations as well as reduced postoperative pain and decreased hospitalization periods. The solution of eTEP demonstrates potential to serve as a superior choice than IPOM plus for treating umbilical hernias. Further research involving multiple hospitals will need to confirm these study findings.